ANALISIS NILAI KEAMANAN TUBUH BENDUNGAN JLANTAH KARANGANYAR - Tri Prandono Sutardjo; Reffi Lovita Sari Purwina Awandian (Jurnal Humaniora & Sosial Sains, 2025)
Dams as structures used to store water must be designed safely in all conditions, including the safety of the dam body. Based on the Indonesian earthquake distribution map, the Jlantah Dam is included in the earthquake risk class 4 (extreme). According to the guidelines for dynamic analysis of embankment dams from the Directorate General of Water Resources, the selection of the earthquake return period without damage to the Operating Basis Earthquake (OBE) is 100 years and the return period with damage without collapse of the Maximum Design Earthquake (MDE) is 1,000 years. For this reason, an analysis of the safety value of the Jlantah dam body is needed. The purpose of this study was to determine the safety value of the Jlantah dam body without earthquakes and earthquake loads using quantitative analysis methods. This study used dam technical data, dam geometry data and Jlantah dam soil data obtained from BBWS BS. Data processing was carried out by determining design parameters, determining earthquake coefficients and analyzing the stability of the dam body using the SLOOPE / W program. From the results of the research and analysis conducted, it can be concluded that the analysis of the safety value of the Jlantah dam in flood, normal and rapidly receding water level conditions with the Operating Basis Earthquake (OBE) earthquake load and the Maximum Design Earthquake (MDE) earthquake load is in a safe condition.